The Innovation of Digital-Based Instructional Design and Virtual Reality on Geography Subject for 10th Grade High School - Wahyu Pratama Putra; Munawir Yusuf; Agus Effendi (Universitas Pendidikan Ganesha, 2023)
After the COVID-19 pandemic passed, the Indonesian government issued regulations encouraging the recovery of the education sector, such as guidelines for implementing the curriculum in the context of learning recovery. However, this is the problem, and teachers need help adjusting and developing learning plans due to the changes in the curriculum used. Based on these problems, this study aims to develop a digital-based learning design that simultaneously develops and utilizes virtual reality learning media on solar system material. This development research (R&D) type uses the ASSURE model involving media experts, material experts, and instructional design experts as research subjects. The data collection technique used was the provision of a closed questionnaire instrument. Data analysis technique using a percentage quantitative descriptive analysis approach. The results of the data analysis showed that three media experts gave an average score of 3.42, 3 material experts gave an average score of 3.61, and 3 instructional design experts gave a score of 3.31. It was concluded that the learning design and virtual reality media were declared valid and feasible. Learning designs and virtual reality media can be used for Class X SMA in Geography learning.